FEAR CONDITIONING AND EXTINCTION IN ANXIOUS AND NONANXIOUS YOUTH AND ADULTS: EXAMINING A NOVEL DEVELOPMENTALLY APPROPRIATE FEAR-CONDITIONING TASK - Shechner, Tomer (Depress Anxiety, 2014)
BACKGROUND: Fear conditioning and extinction have been implicated in the pathogenesis of anxiety disorders. However, due to ethical and methodological limitations, few studies have examined these learning processes across development, particularly among anxious individuals. The present study examined differences in fear conditioning and extinction in anxious and nonanxious youth and adults using a novel task designed to be more tolerable for children than existing paradigms. METHODS: Twenty-two anxious adults, 15 anxious youth, 30 healthy adults, and 17 healthy youth completed two discriminative fear- conditioning tasks. A well-validated task paired a woman’s fearful face with a scream as the unconditioned stimulus. The novel task paired a bell with an aversive alarm as the unconditioned stimulus. Self-reported fear, skin conductance response, and fear-potentiated startle eye blink were measured. RESULTS: Both tasks were well tolerated and elicited fear responses with moderate stability. Anxious youth and adults reported overall greater fear than healthy participants during the tasks, although no group differences occurred in discriminative fear conditioning or extinction, as assessed by self-report or physiology. CONCLUSION: The novel bell-conditioning task is potent in eliciting fear responses but tolerable for pediatric and anxious populations. Our findings are consistent with prior studies that have shown comparable fear learning processes in anxious and nonanxious youth, but dissimilar from studies exhibiting between-group differences in extinction. Given the limited research on fear conditioning in youth, methodological issues and suggestions for future work are discussed. Depression and Anxiety 32:277-288, 2015.